Blood pressure variability, prehypertension, and hypertension in adolescents - Batisky DL (Dove Medical Press, 2012)
Donald L BatiskyEmory Children's Center, Emory University School of Medicine, Atlanta, GA, USAAbstract: Medical conditions diagnosed during adolescence may have long term impacts on the health of an individual. As a result, identifying cardiovascular risk factors earlier in life such as prehypertension (pre-HTN) and hypertension (HTN) can have significant benefits across an individual's lifespan. Diagnosing elevated blood pressure (BP) during adolescence can be difficult, partially due to the natural variability that occurs during this period of life. Levels of BP that define adolescent prehypertension/hypertension are provided as well as an abridged review of BP variability across research groups. Strategies for BP management of adolescents are considered, with the primary focus on nonpharmacologic interventions.Keywords: HTN, pre-HTN, overweight, obesity, BP, body mass index, BMI